Myocardial infarction in young adults: are the risk profile and mortality outcomes different from older patients?. (11th May 2021) - Borges-Rosa, J; Campos, GM; Martinho, S; Almeida, JL; Goncalves, V; Ferreira, C; Freitas, AA; Milner, J; Ferreira, JA; Monteiro, S; Goncalves, F; Monteiro, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: The incidence of acute myocardial infarction (AMI) among young patients is increasing. The YOUNG-MI Registry reported that those under 40 years had similar risk profiles and outcomes compared to those aged 41 to 50. We aimed to evaluate cardiovascular risk factors and mortality outcomes in two age cohorts from southern European. Methods: We retrospectively evaluated 4758 patients admitted to our coronary intensive care unit between 2004 and 2017 with AMI. We only included patients <60 years in two subgroups: cohort A < 50 years and cohort B 50-60 years.  Results: From the 1233 patients included (mean age 50.5 ± 6.5 years, 82.2% male), 53% had STEMI. Cohort B had higher rates of hypertension (59.8 vs. 42.9%, p < 0.001), diabetes (41.8 vs. 28.9%, p < 0.001), and dyslipidemia (59.4 vs. 46.4%, p < 0.001), while cohort A had higher rates of familial premature coronary artery disease (20.9 vs. 13.2%, p < 0.001) and smoking habits (54.4 vs. 40.0%, p < 0.001). Regarding coronary angiography, cohort B had higher rates of obstructive disease in each epicardial artery, except for left main involvement and non-obstructive disease (Fig. 1). Cohort A had lower all-cause mortality rates at the index hospitalization (1.3 vs. 3.2%, p = 0.045), 6-months (2.9 vs.5.4, p = 0.038), 1-year (3.1 vs. 6.3%, p = 0.014), and 3-years (3.6 vs 8.4, p = 0.001). After multivariable adjustment, we found no relationship between age cohorts and all-cause mortality for any follow-up timing: HR 1.57 (95% CI 0.56-4.37), 1.37 (95% CI 0.50-3.74), and 0.92 (95% CI 0.35-2.39) at 6-months, 1-year, and 3-years, respectively. Conclusion: Among patients who suffer AMI, those under 50 years old have a different risk profile, compared to the 50-60 years cohort. However, there is no significant difference in all-cause mortality.